Intimate Partner Violence in Iran: Factors Associated With Physical Aggression Victimization and Perpetration. Issue 5 (March 2021) - Nikparvar, Fatemeh; Stith, Sandra; Anderson, Jared; Panaghi, Laily
Intimate partner violence (IPV) is identified as a human rights abuse which happens everywhere regardless of the society and culture. This study addressed risk markers for physical IPV victimization and perpetration among men and women in Tehran, Iran. Data were collected from 250 participants (111 men and 139 women) in Tehran who reported perpetrating or experiencing IPV at least once in the past year. In this article, we sought to understand risk markers for both male and female physical IPV victimization and perpetration and whether these risk markers differed by gender. We used regression analyses to test two models with males and females separately. Results indicated that for males, physical aggression perpetration was a significant predictor of physical aggression victimization, and physical aggression victimization, psychological aggression victimization, and psychological aggression perpetration were significant predictors of physical aggression perpetration. For females, psychological aggression victimization and physical aggression perpetration were significant predictors of physical aggression victimization, and physical aggression victimization and psychological aggression perpetration were significant predictors of physical aggression perpetration. These results can be helpful in efforts to develop effective interventions for people at risk of IPV in Iran.